Opioid Antagonists May Reverse Endogenous Opiate "Dependence" in the Treatment of Self-Injurious Behavior - Curt A. Sandman; Aaron S. Kemp (MDPI AG, 2011)
Self-injurious behavior (SIB) is a primary reason that individuals with neurodevelopmental disabilities (NDD) are either retained in restrictive environments or are administered psychotropic medication. There are no known causes and no universally accepted treatments for this complex behavior among individuals with NDD. There is developing evidence, however, that individuals exhibiting SIB have a disturbance of the opiate-mediated pain and pleasure system. One hypothesis is that SIB reflects insensitivity to pain and general sensory depression (hypoalgesia), perhaps related to chronic elevation of endogenous opiates. For instance, many self-injurious individuals do not exhibit the usual signs of pain after their "injurious" behavior. Moreover, for some individuals the addictive properties of elevated endogenous opiates (euphoria) may be responsible for maintaining their SIB. In this perspective, SIB may be viewed as an addiction because it supplies the "fix" for tolerant, down-regulated opiate receptors. Reports that levels of endogenous opiates at rest and after SIB episodes predict positive responses to opiate blockers (e.g., naltrexone) provide further support for opiate-mediated SIB and form the basis for a rational treatment strategy. Although the long term effects of opiate blockers on SIB are unknown, reduction in SIB following acute treatment provides support that a specific biological system may be dysregulated in a subgroup of patients. It is concluded that naltrexone produces a clinically significant reduction in the serious and life-threatening behavior of self injury for individuals who have not been responsive to any other type of treatment. Several suggestions and cautions are provided for regimens of naltrexone treatment of SIB.